Connectivity between mitochondrial functions and psychiatric disorders - Hroudová, Jana; Fišar, Zdeněk (Psychiatry and clinical neurosciences, 2011)
Mitochondria provide most of the energy production in cells. They are involved in the regulation of free radicals, calcium buffering, and redox signaling and take part in the intrinsic pathway of apoptosis. Mutations or polymorphisms of mitochondrial DNA, mitochondria-mediated oxidative stress, decrease of adenosine triphosphate production, changes of intracellular calcium and oxidative stress are concerned in various diseases. There is increasing evidence that impaired functions of mitochondria are associated with mood disorders. It is suggested that disturbed energetic metabolism and/or reactive oxygen species production take part in the pathophysiology of mood disorders and could participate in the therapeutic effects or side-effects of antidepressants and mood stabilizers.
Keywords: mitochondriální DNA; oxidační stres; DNA, Mitochondrial; Mitochondria; Calcium; Mental Disorders; reaktivní formy kyslíku; vápník; Neuronal Plasticity; duševní poruchy; Models, Biological; Reactive Oxygen Species; lidé; biologické modely; Humans; apoptóza; antidepresiva; Antipsychotic Agents; Oxidative Stress; Antidepressive Agents; neuroplasticita; mitochondrie; antipsychotika; Apoptosis